Kawasan Ekonomi Khusus (KEK) dan Pembangunan Ekonomi: Sebuah Studi Komparatif Indonesia dan Cina - Darmastuti, Shanti; Afrimadona; Kurniawan, Andi (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2018)
Special Economic Zone (SEZ) has been one of the main drivers of economic development in many developing countries. One of the success stories of these SEZs is China. The giant country began its SEZs at the beginning of the 1980s and in several years, these SEZs have branched out elsewhere in the country. The ability of these SEZs to attract investors and spur economic growth in neighboring regions leading eventually to overall China’s economic success cannot be separated from the strong commitment of the Chinese government to developing these zones. However, commitment turns out not to be the only factor for the success of SEZ program. The ability to devise strategic plan considering all factors including the socio-cultural and geostrategic variables is also the key to the success. What China has done to develop its SEZs can be an invaluable lesson for Indonesia who aspires to develop its own SEZs in order to spur regional growth.